First is almost trivial to show that $N$ is a normal subgroup. I define the map $f$ as follows: $gN\mapsto (gN_1, \ldots gN_k)$.
$f$ is **well-defined**. For is $hN=kN\iff h^{-1}k \in N$ and so $h^{-1}k \in N_i$ for all $i$. Hence $(hN_1, \ldots hN_k)=(kN_1, \ldots kN_k)$ as desired.
$f$ is **one to one**. If $(hN_1, \ldots hN_k)=(kN_1, \ldots kN_k)$, it follows that $\forall i (h^{-1}k \in N_i)$ i.e. $h^{-1}k\in N$ as desired.
$f$ is **homomorphism** Clearly we have a structure of a group. Then $f(gN kN)=f(gkN)$, so $(gkN_1, \ldots gk_k)=(gN_1kN_1, \ldots gN_kkN_k)=f(gN)f(hN)$